Assessment of the neuromuscular characteristics of the flexo-extension muscles of knee by tensiomyography in elite soccer players: a systematic review - Lorigados Pérez, Jesús; Bustamante-Sánchez, Álvaro (Frontiers in Sports and Active Living, 2025)
IntroductionThe objective was to summarize the usefulness of tensiomyography (TMG) as a monitoring tool to evaluate the neuromuscular characteristics of the knee flexor and extensor muscles in elite male soccer players.MethodsA search of Pubmed, Web of Science (WOS), SPORTdiscus and Scopus databases was performed using the PRISMA methodology.ResultsThe results obtained suggest that TMG can provide information not only on individual responses to training, but also on neuromuscular and functional fatigue and lateral asymmetries.DiscussionThe monitoring of the evolution of the neuromuscular state during the season in soccer players, can help coaches and medical staff to identify the initial characteristics that are relevant for the planning and programming of training, and that these changes can be monitored through the study of the modification of mechanical muscle characteristics assessed by tensiomyography.ConclusionThe TMG is a useful tool for evaluating the neuromuscular characteristics of the knee flexor and extensor muscles in elite male footballers.